Debt Policy, Tax Planning, and Tax Risk on Financial Performance : Evidence from Indonesian Healthcare Sectors - Irawati, Wiwit; Barli, Harry; Wulandari, Rosita; Sugiyarti, Listya (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
This study aims to determine the effect of debt policy, tax planning, and tax risk on financial performance in Indonesian healthcare sector. The subject of the research was the companies in the healthcare sector listed on the IDX in 2019-2022. The sample companies are selected with purposive sampling techniques to support the research findings. The data analysis technique was supported by Eviews software using multiple linier regression. The study resulted in the debt policy and tax planning variables partially affect financial performance, while tax risk has no effect on financial performance. The study uses secondary data. If supplemented with in-depth interviews with competent sources, more in-depth analysis is likely. The results showed that in the healthcare sector with tax incentives provided by the government, financial performance was not affected, it is recommended that the government, in this case the Director General of Taxes, be more selective in providing incentives and more disciplined in its supervision. This study draws on updated and recent secondary data so that it can serve as an illustration for the basis of government tax policy making in related sectors. This research also examines the effect of tax risk on financial performance which has not been studied much before.